The moral aspects of the philosophical anthropology of E. Fromm and M. Scheler - Shafarevich, Irina O. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
The article examines the moral aspects of the philosophy of E. Fromm and M. Scheler. The author considers the work of E. Fromm and M. Scheler as an attempt to solve ethical problems through an appeal to the ideas of philosophical anthropo logy. Thinkers criticized modern civilization and put forward genuine human values that should not be imposed as formal norms, but should be revealed to the individual from within as characteristics of its true existence. In this case, E. Fromm a new assessment of human behavior and insists on a radical transformation of the entire system of human value orientations. In turn, M. Scheler pursues a large-scale goal: the restoration or innovative justification of the «material ethics of values», which guarantees the protection of ethics from any social stagnation and involves the return of trust in it on the part of people.
Keywords: E. Fromm’s ethics; M. Scheler’s ethical views; philosophical anthropology